The attitude of Japanese newspapers in narrating disaster events: Appraisal in critical discourse study - Dian Puspita; Budi Eko Pranoto (Universitas Syiah Kuala, 2021)
During the event of disasters, news media are considered as the most visible of all parties involved in the response and rehabilitation. News media frame disaster events in certain attitudes, which then significantly resonates with the magnitude of the disaster. This research aims at investigating the attitude of the Japanese newspaper in narrating disaster events. Using the descriptive qualitative method, this study adopts the appraisal theory (Martin White, 2005) to embed and reveal appraisal in attitude features. The data were taken from three Japanese online newspapers reporting disaster events from 2019 to early 2020 with a total number of 100 articles. The findings show that of all attitudinal features, judgement is found as the most frequent source, followed by appreciation, and affect. It reveals newspapers’ tendency to emphasize the attitude and to construe the evaluation toward the events or phenomena rather than revealing the feelings or emotions experienced by the emoter(s). Interestingly, the distribution of the attitudinal implies the attitude of Japanese newspapers on reporting disaster which is highly emphasized on admiring, criticizing, praise, and condemning disaster events. It is also found that the negative features are slightly higher than the positive ones, but to refer to the phenomena rather than the victims. This lexical strategy proves that Japanese newspapers play the role in mainstreaming disaster management policy which focuses on the reconstruction and rehabilitation after disaster events.